2020
DOI: 10.1159/000505192
|View full text |Cite
|
Sign up to set email alerts
|

Parotidectomy via Individualized Mini-Blair Incision

Abstract: Background: The modified Blair incision is the standard facial incision for the vast majority of parotid gland lesions. We utilize three types of incisions: "classic mini-Blair" for parotid body tumors, "cervical mini-Blair" for parotid tail tumors, and "vertical mini-Blair" for anterior parotid tumors. In this study, we describe the surgical and esthetic outcomes of these individually tailored incisions. Methods: Patients undergoing parotidectomy between 2011 and 2013 were included. The surgical outcomes and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Besides its significant advantages, the modified Blair approach has several disadvantages. 22 Identification of the facial nerve and its branches by this approach requires experience and increases the time of surgery. However, identifying and separating the individual branches of the nerve reduces the probability of paresthesia when performed under direct visual supervision.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides its significant advantages, the modified Blair approach has several disadvantages. 22 Identification of the facial nerve and its branches by this approach requires experience and increases the time of surgery. However, identifying and separating the individual branches of the nerve reduces the probability of paresthesia when performed under direct visual supervision.…”
Section: Discussionmentioning
confidence: 99%
“…However, the periauricular scar is very well camouflaged and can be invisible with a carefully designed incision in a skin crease. 6 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…The VSI involves only the pre-and postauricular incisions, without any hairline or upper cervical inclusion. As a result, this method can be used to handle all superficial parotid regions, including both the superior and anterior divisions, while leading to minimal scarring [9].…”
Section: Discussionmentioning
confidence: 99%
“…The greatest change in the evolution of parotid surgery was the introduction of a modified/partial superficial parotidectomy, which leaves as much normal parotid tissue as possible and removes the tumor with a cuff of normal parotid tissue around it [ 17 , 21 ]. Other modifications for incisions, including minimal skin incisions [ 11 ] or cosmetic incisions [ 22 ] have seldom been suggested. Studies using self-assessment scores have shown that surgical drains are associated with a significant increase in patients' anxiety and pain as well as reduced comfort [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…All surgeries were performed by the same high-volume head and neck surgeon (A.K.). An individualized modified mini-Blair incision [ 11 ] was used in all patients. The relevant facial nerve branches or trunk were identified according to the location of the tumor and the surgical needs.…”
Section: Surgical Proceduresmentioning
confidence: 99%